An update on the use of lenalidomide for the treatment of multiple myeloma. (August 2015) - Zagouri, Flora; Terpos, Evangelos; Kastritis, Efstathios; Dimopoulos, Meletios-Athanasios
<x xml:space="preserve">Abstract</x> Introduction: <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=Lenalidomide&logicalOpe1=OR&field2=articletitle&text2=Lenalidomide&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">Lenalidomide, an immunomodulatory agent with unique mechanism of action, represents the cornerstone in the treatment of patients with multiple myeloma (MM) providing rapid and sustained control of the disease with a manageable safety profile. Areas covered: This review article, synthesizing all available data coming from trials and evaluating the efficacy and safety of lenalidomide in patients with MM, tries to provide to the clinicians with an easy-to-grasp synopsis of recent and clinically meaningful advances on the field. Expert opinion: Lenalidomide combined with dexamethasone is a safe and effective option for newly diagnosed MM patients ineligible for autologous stem cell transplantation (ASCT). Long-term administration of the agent as continuous treatment for ineligible for ASCT patients or maintenance therapy after ASCT has documented unprecedented progression-free survival improvements, whereas lenalidomide in combination with dexamethasone has shown deep and durable remissions for patients with relapsed and/or refractory disease.